From complexity to simplicity – how chasing success stories affects gendered NGO practices. Issue 4 (18th May 2020) - Kloster, Maren Olene
ABSTRACT: This article argues that the "production" of success has become crucial for NGOs to manage their individual brand and secure funding within the contemporary global health and development landscape. Based on an empirical study of a Save the Children project in Malawi aimed at reducing teenage pregnancies by retaining girls in school, it illustrates how gender has become de-politicised within global health. Furthermore, it also shows how their changing role and growing pressure on NGOs to achieve impact and success stories affect NGOs' ability to represent and understand the lives of women and girls.